TINJAUAN HUKUM TERHADAP PERAN SERTA PEMERINTAH DESA DALAM PEMBINAAN KEARIFAN LOKAL DI KECAMATAN SOROMANDI, BIMA, NUSA TENGGARA BARAT - Jum Anggriani; Indah Harlina; Mirsadin (Jurnal Hukum dan Bisnis (Selisik), 2021)
Through Law Number 6 of 2014 it opens space for governance in accordancewith the characteristics, culture, and local wisdom of each region. Soromandi subdistrict, for example, is one of the areas in Bima district which has a characteristicin governance that is still firmly held, namely a strong mutual cooperation culturethat is still alive today. From this description, two main problems can be drawn; 1)What is the role of the village government in maintaining local wisdom inSoromandi District, 2) What are the efforts made by the village government inincreasing local wisdom in Soromandi District.This research is normative andempirical legal research, namely legal research that examines the factualimplementation or implementation of positive legal provisions in every particular SELISIK - VOLUME 7, NOMOR 1, JUNI 2021ISSN:2460-4798 (PRINT) & 2685-6816 (ONLINE)117legal event that occurs in society. The Soromandi District Village Governmentcarries out its role as an extension of the government's arm to regulate and manageits village households properly, by participating in maintaining and preservingwisdom in the villages of Soromandi District. Efforts made by the government inimproving local wisdom in Soromandi villages have been going quite well, this canbe seen from the continued preservation of local wisdom in Soromandi sub-districtvillages such as: religious, helping nature, solidarity, mutual cooperation,deliberation. consensus, the principle of kinship and sharing in the lives of itscitizens through traditional rituals that are still valid